A Case for Monetary Reform - Pierce, James L. (American Economic Review, 1979)
Any paper on U.S. monetary reform must consider reform of the Federal Reserve System. This paper considers reforms of the Federal Reserve that should enhance the quality of monetary policy. Two kinds of reforms are considered: 1) changes in the internal institutional structure of the Federal Reserve that should enhance the quality of its monetary policy decisions; 2) changes in the powers of the Federal Reserve to impose reserve requirements that should enhance the efficacy of the policies themselves.